Forward and Inverse Kinematic on Wheeled Soccer Robot - La Ode Muhamad Idris; Sri Arttini Dwi Prasetyowati; Imam Much Ibnu Subroto (Journal of Telematics and Informatics, 2018)
In this research rotary encoder sensor and gyroscope sensor are used as main sensor for moving wheeled soccer robot. Rotary encoder is used to measure the speed and distance of each robot wheel and the gyroscope is used to measure the orientation of the robot, then both of them expressed in cartesian diagrams (x, y, θ). A rotary encoder type magnetic incremental encoder is used in this research and it mounted on each wheel. Inverse kinematic and forward kinematic are used to control the movement of the robot when positioning in the field or making decision when kicking the ball towards the opponent’s side and the other decision. From the test results, robot can move to any direction from the starting position to the end position with a different robot orientation and robot can measure the coordinates of the robot with average error of x = 5.37%, y = 5.2%, and Theta = 0.26%. The robot is also able to move in the direction of the coordinates given with a traveling time of 3-4 seconds.